Synthesis of Wafer‐Scale Graphene with Chemical Vapor Deposition for Electronic Device Applications. Issue 7 (23rd April 2021) - Sun, Baojun; Pang, Jinbo; Cheng, Qilin; Zhang, Shu; Li, Yufen; Zhang, Congcong; Sun, Dehui; Ibarlucea, Bergoi; Li, Yang; Chen, Duo; Fan, Huaimin; Han, Qingfang; et al.
Abstract: The first isolation of graphene opens the avenue for new platforms for physics, electronic engineering, and materials sciences. Among several kinds of synthesis approaches, chemical vapor deposition is most promising for the growth at wafer‐scale, which is compatible with the Si‐based electronic device integration protocols. In this review, the types, properties, and synthesis methods of graphene are first introduced. Many details of wafer‐scale graphene synthesis by chemical vapor deposition strategies are given, including the wafer‐scale single crystal metal and alloy preparation, roll to roll synthesis over Cu, roll to roll electrochemical transfer technique. Besides, the batch‐to‐batch synthesis are highlighted for direct graphene over dielectric substrates such as sapphire and Si/SiO2 . The electronic transport and transparent conductance of the wafer‐scale graphene are compared with high‐quality single crystal. The progress and proof‐of‐the‐concept are briefly recalled in graphene‐based electronics such as transistors, sensors, integrated circuits, and spin transport valves. Eventually, the readers are provoked with the current challenges as well as the future opportunities.​ Abstract : The recent advances of chemical vapor deposition have been summarized for wafer‐scale graphene growth. The progress in two strategies, i.e., roll‐to‐roll and batch‐to‐batch are compared based on the application potentials in transparent conducting film and transistor devices. For epitaxial graphene formation, meter long single‐crystal metals are fabricated as substrates. The reports in proof‐of‐concept, i.e., spintronics, logic circuits are reviewed.